Analisis Yuridis Terhadap Mekanisme Perjanjian Sewa-Menyewa Excavator dan Upaya Penyelesaian Sengketa Wanprestasi Berdasarkan Ketentuan KUHPerdata - Ramadani, Reva Fitri; Natasya, Amanda Mutiara; Azzahra, Viola Farica; Ramadhani, Dwi Aryanti; Pebrianti, Selma Dwi Anaya (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Lease according to Subekti is when the first party is able and will hand over an object that will be used for a certain period of time to the second party who will agree to pay a predetermined price related to the use for a predetermined time. Leasing is done by making a contract or agreement. An agreement is an agreement between two parties that must be fulfilled by each party. When the debtor does not fulfill his obligations according to the agreement, then it can be called a default. The obligation of one party is to hand over the goods to the other party for use, and the other party is obliged to pay the rental fee. Therefore, the goods are not handed over to be owned as in buying and selling, but are used only to enjoy the benefits. This research was conducted with the aim of knowing how the legal mechanism of the Excavator Lease agreement as stipulated in the Civil Code (KUHPerdata) and various legal remedies related to the settlement of default problems in Excavator rental. The research method used is using a juridical-normative approach.